Drawing Sovereignty: The Museum Work of Sámi Artist Ánddir Ivvár Ivvár/Iver Jåks. - Stien, Hanne Hammer (Critical Arts: A South-North Journal of Cultural & Media Studies, 2025)
From the first part of the 1950s until the mid-1980s, the Sámi artist Ánddir Ivvár Ivvár/Iver Jåks (1932–2007) played an influential role in the making of exhibitions displaying Sámi culture and art, both in a Norwegian and Sámi museum context. This article examines Jåks museum work with a specific focus on his drawings of Sámi objects from museum collections, duodji in Northern Sámi. The author argues that Jåks' methodological application of drawing contributed to the development of a visual imagery deeply rooted in a Sámi way of thinking, seeing, and doing. Consequently, the article shows that Jåks' museum work can be read as an act of doing sovereignty through the act of drawing.